2006
DOI: 10.1111/j.1399-0012.2006.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

The advantage of allocating kidneys from old cadaveric donors to old recipients: a single‐center experience

Abstract: We did not find a relevant difference in the outcome between young and old kidney transplants in old recipients after this long observation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
13
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
7
13
1
Order By: Relevance
“…Since older individuals with comorbidities are more prone to infectious diseases, implementation of less-potent immunosuppressive regimens could be advocated. On the other hand, BPAR rates in our study cohort were quite high, but still compatible with reports by others [11,13,15]. However, graft loss due to chronic rejection was a rare event.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Since older individuals with comorbidities are more prone to infectious diseases, implementation of less-potent immunosuppressive regimens could be advocated. On the other hand, BPAR rates in our study cohort were quite high, but still compatible with reports by others [11,13,15]. However, graft loss due to chronic rejection was a rare event.…”
Section: Discussionsupporting
confidence: 78%
“…In particular, we wanted to extend previous analyses [11][12][13][14][15][16] by including outcome data that have so far not been studied in detail, including the risk of de-novo DSA development, BK viral infection rate, and tumor development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that the rate of DGF did not differ in our study group from control groups, and rate of DGF was in the range found by other authors. 5,[15][16][17] In addition, we did not find a negative impact of DGF on graft survival in the ESP recipients as described by others. 5,17 The favorable outcome in our study may be due to the very short CIT, because prolonged CIT is strongly associated with an increased rate of DGF.…”
supporting
confidence: 63%
“…14 Our task is to select the right patient for the waiting list and to perform a close follow-up after KTX. 15,17 How can donor renal capacity and ex- a histologic score for donors aged Ն60 for the decision to transplant one, both, or no kidney of the same donor 21,22 ; and a score of demographic, medical, and CIT. 23 Nevertheless, we found that donor creatinine clearance according to Cockcroft-Gault in combination with the aforementioned inclusion criteria are sufficiently reliable and easily applicable tools to predict graft outcome of ECD kidneys.…”
mentioning
confidence: 99%